2006
DOI: 10.1016/j.ijms.2006.03.016
|View full text |Cite
|
Sign up to set email alerts
|

G-quadruplexes in telomeric repeats are conserved in a solvent-free environment

Abstract: The structural properties of G-quadruplex forming sequences, such as the human telomeric repeat d(T 2 AG 3 ) n , are of great interest due to their role in cancer and cellular aging. To determine if G-quadruplexes are present in a sol vent-free environment, different lengths of the telomeric repeat d(T 2 AG 3 ) n (where n= 1, 2, 4 and 6) and dTG 4 T were investigated with mass spectrometry, ion mobility and molecular dynamics calculations. Nano-ESI-MS illustrated quadruplex stoichiometries compatible with G-qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
114
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(120 citation statements)
references
References 57 publications
6
114
0
Order By: Relevance
“…These gas-phase structures are considered to reflect the quadruplex structures in°solution° [15][16][17][18][19][20].°A°recent°quadruplex°study°by Bowers' group suggests that ESI can be used to characterize the quadruplexes and their interactions with ligands because the quadruplex ions at lower charge states maintain their structures through the electro- spray and desolvation process if no activating energies are°applied°to°the°system° [19].°In°the°present°work, individual bimolecular quadruplexes are detected in the gas phase. NMR solution structures show that the four-sequence closely related DNA strands form distinct topological bimolecular quadruplexes in solution, as°shown°in°Figure°1b-e.°The°presence°of°monovalent cations, such as Na ϩ , K ϩ , and NH 4 ϩ , is necessary to coordinate between adjacent G-quartets and to stabilize the quadruplex structure.…”
Section: Detection Of the Bimolecular Dna Quadruplexesmentioning
confidence: 99%
See 1 more Smart Citation
“…These gas-phase structures are considered to reflect the quadruplex structures in°solution° [15][16][17][18][19][20].°A°recent°quadruplex°study°by Bowers' group suggests that ESI can be used to characterize the quadruplexes and their interactions with ligands because the quadruplex ions at lower charge states maintain their structures through the electro- spray and desolvation process if no activating energies are°applied°to°the°system° [19].°In°the°present°work, individual bimolecular quadruplexes are detected in the gas phase. NMR solution structures show that the four-sequence closely related DNA strands form distinct topological bimolecular quadruplexes in solution, as°shown°in°Figure°1b-e.°The°presence°of°monovalent cations, such as Na ϩ , K ϩ , and NH 4 ϩ , is necessary to coordinate between adjacent G-quartets and to stabilize the quadruplex structure.…”
Section: Detection Of the Bimolecular Dna Quadruplexesmentioning
confidence: 99%
“…Previous work by ourselves and others have shown that some specific DNA conformations, such as hairpins, triplexes, and quadruplexes formed in solution, can survive in the gas phase [13][14][15][16][17][18][19][20]. This prompted us to explore the structural properties of DNA quadruplexes with ESI-MS so as to add new information concerning them.…”
mentioning
confidence: 99%
“…Measuring the drift time directly linked to the mobility of an ion yields information about its structure because compact ions, which have necessarily relatively small collision cross sections, move faster than extended ones, which have large collision cross sections. The gas-phase conformations of many oligonucleotides have been investigated by ion mobility: deprotonated mononucleotides [19,20], dinucleotides [21], trinucleotides [22], deprotonated oligothymidines [23], DNA complexes [24], G-quadruplex [25,26], etc.…”
mentioning
confidence: 99%
“…For example, the dissociation profiles of a series of 6-, 8-, and 12-base pair selfcomplementary duplexes have been shown to correspond to the known solution melting behavior of DNA, demonstrating the utility of CAD to provide relative comparisons of the gas-phase stabilities of DNA duplexes [30]. Fewer studies have been undertaken to elucidate the gas-phase structures or stabilities of quadruplex DNA [32][33][34][35][36][37]. One recent study focused on using ion mobility mass spectrometry and molecular dynamics simulations to examine gas-phase conformations of quadruplexes with different lengths of the telomeric repeat d(TTAGGG) n where n ϭ 1, 2, 4, and 6 [33].…”
mentioning
confidence: 99%